The Effectiveness of Electronic Administration in Decision-Making Process in Public Schools in Ajloun Governorate from the Point of view of Principals - Alananzeh, Alaaldin Hussein Ozbi (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the degree of the effectiveness of electronic administration in decision-making process in public schools in Ajloun governorate from the point of view of principals. To achieve the objectives of the study, the researcher used the descriptive analysis approach, the sample of study consisted from (110) female and male principals, and a questionnaire for data collection; it consisted of (20) statements. The results indicated that the degree of the effectiveness of electronic administration in decision-making process in public schools in Ajloun governorate from the point of view of principals was high with average (4.20 out of 5). Furthermore, there were no statistical significant differences at (α ≤ 0.05) in the variable of principal’s sex. However, there were statistically significant differences due to the years of experience of the participants in favor of (10 years and more). Based on the results, the researcher presented a number of recommendations and proposals, to enhance the effectiveness of electronic administration in decision-making process in Ajloun, and the whole of the Kingdom and the Arab countries.